Regiospecific azidoiodination of alkenes with sodium periodate, potassium iodide, and sodium azide: a high-yield synthesis of beta-iodoazides - Chouthaiwale, Pandurang V.; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Synthesis-Stuttgart, 2010)
The combination of sodium periodate, potassium iodide, and sodium azide has been found to be an efficient, simple, and inexpensive reagent system for azidoiodination of alkenes. The regiospecific 1,2-azidoiodination proceeds in an anti-Markovnikov fashion to produce beta-iodoazides in excellent yields.
Keywords: alkenes; azides; azidoiodination; beta-iodoazides; regio-specific

Regioselective oxo-amination of alkenes and enol ethers with N-bromosuccinimide-dimethyl sulfoxide combination: a facile synthesis of alpha-amino-ketones and esters - Prasad, Pragati K.; Reddi, Rambabu N.; Sudalai, Arumugam (Organic Letters, 2016)
An unprecedented conversion of alkenes and enol ethers to the corresponding a-imido carbonyl compounds with excellent regioselectivity and yields has been developed. This oxo-amination process employs readily available N-bromosuccinimide (NBS) and secondary amines as N-sources and dimethyl sulfoxide (DMSO) as the oxidant and also leads to the production of amino alcohols in a single step on reduction, thus broadening the scope of this operationally simple reaction. For the first time, the formation of reactive Me2S+-O-Br species generated by the interaction of NBS with DMSO has been proven.